1970
DOI: 10.3329/jbau.v7i1.4969
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-intestinal helminths of ducks: Some Epidemiologic and pathologic aspects

Abstract: A total of 206 ducks were subjected to routine postmortem examinations from July 2007 to June 2008. Of the ducks examined, 167 (81.1 %) were infected by one/more species of gastro-intestinal helminths. A total of ten species of helminth parasites were recovered from gastrointestinal tract, of which four species were trematodes namely: Echinostoma revolutum, Notocotylus attenuatus, Hypoderaeum conoideum and Echinoparyphium recurvatum; two were nematodes, namely, Amidostomum anseris, Capillaria contorta; two wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 3 publications
3
17
0
3
Order By: Relevance
“…Borah et al (2018) recorded the similar data with where E. revolutum was 24.07% prevalent. Yousuf et al (2009) also found that the prevalence of gastrointestinal helminth was significantly (p < 0.05) higher in female ducks (82.7%) than male ducks (77.6%). In male, E. recurvatum displayed the maximum prevalence (25%).…”
Section: Resultsmentioning
confidence: 72%
“…Borah et al (2018) recorded the similar data with where E. revolutum was 24.07% prevalent. Yousuf et al (2009) also found that the prevalence of gastrointestinal helminth was significantly (p < 0.05) higher in female ducks (82.7%) than male ducks (77.6%). In male, E. recurvatum displayed the maximum prevalence (25%).…”
Section: Resultsmentioning
confidence: 72%
“…Consequently these intestinal glands fused and come out as a cellular mass (Figure 4) and degeneration of intestinal glands, necrosis and infiltrated caecal lamina propria were also observed ( Figure 5). The infiltrated colon lamina proparia present in the intestine of duck infected by Heterakis gallinarum [18]. Nematode parasite cause hemorrhagic enteritis and sinusitis in the intestine therefore sever destruction and deterioration of microvilli observed in duck flocks [19].…”
Section: Resultsmentioning
confidence: 99%
“…were also found in the present study. Prevalence of gastrointestinal parasites had seasonal variability as documented in different bird species by Yousuf et al (2009). Parasitic infections hampered growth and egg production and infected birds were more susceptible to other infections (Dranzoa et al 1999).…”
Section: Resultsmentioning
confidence: 99%